Demitologisasi politik Indonesia mengusung elitisisme dalam Orde Baru - Adi Sasono 1943-2016; Syarofin Arba M. F. 1965-; Center for Information and Development Studies (Indonesia). (Jakarta CIDES, 1998)
Politics in Indonesia during the Suharto era; collection of articles.
Includes bibliographical references and index.
Keywords: Elections -- Indonesia; Indonesia -- Politics and government -- 1966-1998.